Evaluation of Gall Bladder Volume in Type 2 Diabetes Mellitus Patients Using Real Time Ultrasonography - KS Jagadeesh; Ashwini M. Patil (Asian Journal of Medical Radiological Research, 2020)
Background: Diabetes mellitus is a group of metabolic diseases characterized by chronic hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Autonomic neuropathy manifests as esophageal dysfunction, nocturnal diarrhea, gall bladder dysfunction, sphincter disturbances, atonic bladder and orthostatic hypotension. The present study aimed to evaluate and compare the gall bladder volume  in fasting and post prandial state by real time ultrasound in Type 2 Diabetes Mellitus (T2DM) patients and healthy controls. Subjects and Methods: In this cross sectional study, 90 subjects were included. Among them, 45 were type 2 diabetes mellitus patients included as cases and 45 age and sex matched healthy controls, who attended the Department of Medicine and Radio-diagnosis, Akash Institute of Medical Sciences & Research Centre, Devanahalli, Bengaluru, Karnaaka. All the study subjects were underwent detailed general and systemic examinations. Under aseptic conditions, 3ml fasting blood samples were collected and used for the estimation of fasting blood sugar, post prandial blood sugar. Gall bladder volume evaluation in fasting and 45 minutes post prandial (standardized fatty meal) state were done in T2DM patients and controls using real time ultrasound (GE Voluson P8 Mechine). Results: In the present study, BMI (24.78 2.31 kg/m2), FBS (160.98 27.99 mg/dl), PPBS (244.31 38.91 mg/dl), Fasting gall bladder volume (33.33 6.42 cm3), post fatty meal gall bladder volume (15.21 6.39 cm3), ejection fraction (49.34 17.29 cm3) were significantly increased in type 2 diabetes mellitus patients compared with healthy controls. Conclusion: The study results conclude that, fasting and post-prandial gallbladder volumes are indicative of gallbladder function. Patients with type 2 diabetes mellitus showed statistically significant impairment of gallbladder function. Gallbladder function may be evaluated routinely in type 2 diabetes mellitus patients.